Acciones que posibilitan la compresión del rol del psicólogo en la intervención en psicología social comunitaria (2011)
Then are released both the processes carried out during practice in the CAPSI in 2011, as well as the actions, strategies and ways to intervene that enabled the understanding of the role of community social psychologist,. It also recognized the community and those who make active agents realize collectively constructed meanings which have an important find, which contributes to the formulation of objectives and goals in the social-community interventions. Also, are the axes of which were focal points in practice, which account for work done, the objectives and results.